Risks of P2P Lending Platforms in China: Modeling Failure Using a Cox Hazard Model. Issue 3 (3rd May 2016) - Li, Jianjun; Hsu, Sara; Chen, Zhang; Chen, Yang
Abstract : P2P lending platforms in China have risen since 2006 but have already experienced problems with fraud and liquidity. In this article, we describe the P2P lending platforms and their associated risks, and discuss and analyze a dataset on failed and nonfailed P2P companies. We find that an increase in the registered capital results in a decrease in the hazard ratio, while an increase in the interest rate results in an increase in the hazard ratio. We discuss policy implications for the P2P lending sector, which can help to reduce risk in the sector while allowing innovation to arise.